2017
DOI: 10.1111/fare.12226
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Sexual Minority Mothers with Trans* Children

Abstract: Eight nonheterosexual (i.e., bisexual, lesbian, bi/pansexual) mothers with trans* children between 6 and 11 years of age participated in semistructured interviews in which they discussed the intersections of their own sexual minority identities with their children's gender identities or expressions. Transfamily theory was utilized to understand how heteronormativity and cisnormativity operated in these families' lives. Initial lack of awareness among most of the mothers regarding trans* identities, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 58 publications
2
47
0
Order By: Relevance
“…The intersections of Jessie's gender expression with Jessie's mother's sexual orientation and gender expression reflect findings of some existing research on LGB‐parent families (Kuvalanka, Allen, Munroe, Goldberg, & Weiner, ; Lev, ). Jessie's mother admitted initial feelings of disappointment with Jessie's attraction to and desire for “all things pink” and other clothes and toys typically deemed to be for girls (at the time of filming, Jessie had not yet socially transitioned).…”
Section: Pink Boysupporting
confidence: 67%
“…The intersections of Jessie's gender expression with Jessie's mother's sexual orientation and gender expression reflect findings of some existing research on LGB‐parent families (Kuvalanka, Allen, Munroe, Goldberg, & Weiner, ; Lev, ). Jessie's mother admitted initial feelings of disappointment with Jessie's attraction to and desire for “all things pink” and other clothes and toys typically deemed to be for girls (at the time of filming, Jessie had not yet socially transitioned).…”
Section: Pink Boysupporting
confidence: 67%
“…Counter to conceptualizing parental reactions to gender variance as acceptance or rejection (Koken, Bimbi, & Parsons, ), findings reveal that transgender youth recalled a lifetime of parents' reactions to gender variance and, over the span of gender identity development, transgender youth perceived acceptance, rejection, negativity, ambiguity, ambivalence, positivity, support, advocacy, and reconciliation. Sexual minority parents of children who identified as transgender have reported similar experiences (Kuvalanka et al, ). Counter to a master narrative that transgender youth are kicked out of or leave their family home due to parental rejection (Yadegarfard et al, ), findings show that most of the participants experienced relational and identity loss—that is, a more psychological form of loss.…”
Section: Discussionmentioning
confidence: 94%
“…Scholars have begun to study complexities among queer families and the ways that they are doing gender, sexuality, and family (Oswald et al, 2009). Notable examples include studies of gay fathers (Carroll, 2018;Goldberg, 2012), second-generation queers (Kuvalanka, 2013;Kuvalanka & Goldberg, 2009), parents of transgender or gender-creative children (Johnson & Benson, 2014;Kuvalanka et al, 2018;Kuvalanka, Weiner, & Mahan, 2014), children of parents who are transgender (Dierckx, Mortelmans, Motmans, & T'Sjoen, 2017), and the recent introduction of transfamily theory (McGuire, Kuvalanka, Catalpa, & Toomey, 2016). Queering traditional approaches to research allows prevailing notions of "the family" to be deconstructed and illuminates diversity among queer and all families (Allen & Demo, 1995).…”
Section: Queer Families Normativities and Intersectionalitymentioning
confidence: 99%
“…Instead, we ask whether it is possible to queer historically singular methods (i.e., only quantitative or qualitative)? That is, in what ways might methods be queered or contribute to queer meanings (Russell, 2016; see also Oswald et al, 2009)? Generally, qualitative approaches lend themselves more readily to understanding and deconstructing the intersectional systems of power and privilege that situate the experience and processes of queer families (Kuvalanka et al, 2018;Oswald et al, 2005Oswald et al, , 2009Rupple et al, 2018). The benefits of qualitative approaches to the study of diverse, queer lives is well demonstrated in the work of Bowleg (2008;Bowleg, Huang, Brooks, Black, & Burkholder, 2003), where participants asserted an experience that is not independently Black, female, or lesbian but that is unique to the contemporaneous relationality of, and social inequalities related to, all three identities (see also Crenshaw, 1989).…”
Section: Quantitative ↔ Qualitativementioning
confidence: 99%